2021
DOI: 10.2514/1.j060143
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of Iced Wing Using Separating Shear Layer Fixed Turbulence Models

Abstract: Aerodynamic prediction of glaze ice accretion on airfoils and wing is studied using the Reynolds-averaged Navier-Stokes method. Two separation fixed turbulence models are developed considering the nonequilibrium characteristics of turbulence. The key ad hoc fix is a term of the local ratio of turbulent production to dissipation, which is used to amplify the destruction term of the 𝝎-equation to increase the eddy viscosity in a separating shear layer of the fully turbulent region. A shear stress limiter is ado… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…If 𝑓 𝑁𝐸 = 1, the model reverts to the original k βˆ’ 𝑣 2 βˆ’ πœ” model. In previous work [27,28], the shear layer region where 𝑃 𝑣 2 /πœ€ > 2.5 is located by the switch function Ξ“ 𝑆𝑆𝐿 , which means that the modification term 𝑓 𝑁𝐸 is turned off where 𝑃 𝑣 2 /πœ€ is less than 2.5. The 𝑅𝑒 𝛺 term in Eq.…”
Section: B the Spf π’Œ βˆ’ 𝒗 𝟐 βˆ’ 𝝎 Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…If 𝑓 𝑁𝐸 = 1, the model reverts to the original k βˆ’ 𝑣 2 βˆ’ πœ” model. In previous work [27,28], the shear layer region where 𝑃 𝑣 2 /πœ€ > 2.5 is located by the switch function Ξ“ 𝑆𝑆𝐿 , which means that the modification term 𝑓 𝑁𝐸 is turned off where 𝑃 𝑣 2 /πœ€ is less than 2.5. The 𝑅𝑒 𝛺 term in Eq.…”
Section: B the Spf π’Œ βˆ’ 𝒗 𝟐 βˆ’ 𝝎 Modelmentioning
confidence: 99%
“…[29] and Li et al [27,28] found that 𝑃 π‘˜ /πœ€ can be greater than 1.8 in the nonequilibrium turbulence region. 𝑃 π‘˜ tends to be significantly larger than Ξ΅ and often as much as 3-4 times greater in a separated shear layer.…”
Section: B the Spf π’Œ βˆ’ 𝒗 𝟐 βˆ’ 𝝎 Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, understanding the precise law of convective heat transfer in the boundary layer of the airframe is a technical prerequisite for the development of an efficient full airfoil anti-icing system [2]. The study of convective heat transfer requires experimental or simulation methods to obtain the evolution of the velocity and temperature fields [3][4][5], but the boundary layer pattern calculated by simulation methods is often a uniform transition [6], which does not reflect the relationship between heat transfer and the flow regime. However, in numerous previous studies, it was found that the effect of heat transfer on the airfoil surface would be influenced by the airfoil flow pattern, and that heating at different regions of the airfoil would have different effects on the flow field and heat transfer efficiency [7].…”
Section: Introductionmentioning
confidence: 99%